URGENSI UNDANG-UNDANG CIPTA KERJA DALAM MENARIK INVESTOR ASING KE INDONESIA - Azharuddin,; Aventina Evanias Saroengoe,; Kuning Hendra Syahputra,; Elvira Pakpahan, (The Juris, 2022)
The role of foreign investment is urgently needed by the Indonesian state during pandemic like now and also a lot of people who need employment. This descriptive research use primary, secondary and tertiary source for data collection. The data analysis used is qualitative. Foreign investment is needed to be able to help the wheels of Indonesian economy because of funds can be used for financing for the business sector and repair of facilities and infrastructure as well creating new jobs. The obstacle that occurs is that there are many overlapping regulations as well as an inadequate skilled workforce. Efforts to gain attract foreign investors are speeding up national economic growth with easy licensing, fair arrangements between workers / laborers and companies, and also legal guarantees.